Sleep deprivation and immunoglobulin E level - Yang, Shih-Wei; Yang, Hui-Fang; Chen, Yuan-Yuei; Chen, Wei-Liang (Frontiers in Medicine, 2022)
Objectives Sleep deprivation is a common issue for modern people and leads to many morbidities and mortality. Some papers also suspected the relationship between Immunoglobulin E (IgE) level and sleep deprivation. The purpose of this article is to make the vicious circle between serum IgE level and sleep deprivation clear. Methods In this study, we included 4,460 population aged around 48 years old respective 2,145 males and 2,315 females enrolled in the National Health and Nutrition Examination Survey (NHANES). Sleep durations were recorded, in hours, in whole numbers by the participants. The levels of total IgE were measured by anti-IgE. All procedures were analyzed using SPSS version 18 (SPSS, Inc., Chicago, IL). Result The statistical significance between higher IgE level and ≤5 h sleep duration was noted (Beta coefficients: 64.04, 95% confidence interval (CI): 2.35, 125.72, P=0.042). In sex difference, the correlation between short sleep duration and high serum IgE levels was noted in male (Beta coefficients: 120.225 (P=0.008)) but not in female. There were no positive findings in the ethnicity-based correlation between serum IgE levels and sleep duration. Conclusion This study indicated that short sleep duration (≤5 h) is associated with higher serum IgE levels, especially in men. Further longitudinal investigations concerning the effect of sleep deprivation on serum IgE might provide a better explanation for the pathophysiology uderlying autoimmune disease and sleep deprivation.